Technical and Tactical Training is the Basis of Wrestlers' Skill - Mo'ydinov Iqboljon Abduxamidovich; Boltaboev Khamidullo Khabibulloevich; Sheraliyeva Sahobat Adhamovna (European Science Publishing, 2023)
It is known that the special skill of a highly qualified player will consist of such basic components as physical, technical, theoretical and volitional training, which, in turn, cannot be imagined without increasing the effectiveness of the training process of young wrestlers
Keywords: physical training, speed and strength, jumping, wrestlers, technical and tactical.